Unabated Serge of Honor Killing: Legal Perspective of Superior Courts in Pakistan - Ch, Sehrish Neik; Jamal, Shumaila (Annals of Human and Social Sciences, 2023)
Honor killings are an invasive type of abuse against gender that occurs in many cultures around the globe. Pakistan continues to experience these phenomena. The research paper examines the State of Pakistan regarding honor killing, its causes, and the efforts undertaken worldwide to lessen such crimes. Due to cultural challenges, discrimination, and brutality against women enforced by the notion of honor dubbed "Izzat," is quite prevalent in Pakistan. As to the Pakistani Constitution, every individual has an unalienable right to life which means the Legislature is bound to enact laws to protect the people' right to physical integrity and respect. Superior courts in Pakistan provided no. of judgments to handle this issue at national level. Still Honor murders are classified by UN as a serious human rights issue that undermines gender equality and is acknowledged as discriminatory towards women’s right. To handle this practice, organizations and legislative frameworks to protect women have been established on a national and worldwide basis. However, honor killings continue to occur and calling for further actions